2008
DOI: 10.1111/j.1365-2850.2007.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of health and health service utilization among homeless and housed psychiatric consumer/survivors

Abstract: Homelessness has a direct impact on health. Homeless individuals report several barriers to accessing health care. Although research exists regarding the utilization of health services for homeless and housed psychiatric consumer/survivors, few studies have compared the perceived health and service utilization of these two groups. The objective of this study was to determine whether or not differences exist between the utilization of health services and the perceptions of health of homeless and housed psychiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 19 publications
1
11
0
5
Order By: Relevance
“…35,36 Further, the high frequency of health-related goals in this study fits with prior research, which has shown that homeless individuals are concerned about and invested in their health. 37 Taken together, these findings indicate that participants value and set various types of goals that are not exclusively drinking related. This point highlights a key tenet of the harm-reduction approach: the importance of viewing participants from a holistic perspective that takes into account various aspects of their life experience beyond their substance use.…”
Section: Discussionmentioning
confidence: 82%
“…35,36 Further, the high frequency of health-related goals in this study fits with prior research, which has shown that homeless individuals are concerned about and invested in their health. 37 Taken together, these findings indicate that participants value and set various types of goals that are not exclusively drinking related. This point highlights a key tenet of the harm-reduction approach: the importance of viewing participants from a holistic perspective that takes into account various aspects of their life experience beyond their substance use.…”
Section: Discussionmentioning
confidence: 82%
“…en ce qui concerne le nombre de maladies chroniques, les personnes itinérantes de cette étude en ont en moyenne trois, un nombre élevé qui va également dans le sens des études antérieures (Forchuk et al, 2008). il est à noter que le type de maladie chronique ne nécessite pas nécessairement l'hospitalisation, mais plutôt des sHA.…”
Section: Discussionunclassified
“…cet instrument a été élaboré pour le projet At Home / chez soi à partir de sept instruments existants : l'Ambulatory Health care record (Guerriere et al, 2006), (Browne, Arpin, corey, Fitch et Gafni, 1990), l'Utilization of Hospital and community services Form (Forchuk et al, 2008), le client socio-demographic and service receipt inventory (chisholm et al, 2000) et le service Use Questionnaire for the continuity of Mental Health services (Adair et al, 2005). Les propriétés psychométriques de ces instruments sont exposées dans Goering et al (2011).…”
Section: Participants Et Participantesunclassified
See 2 more Smart Citations